Alat Penilaian Integritas Organisasi dalam Kerangka Sistem Manajemen Integritas pada Organisasi Sektor Publik: Suatu Tinjauan Alternatif (Lembaga Pengembangan Kinerja Dosen, 2026)
Integrity is a fundamental value in realizing clean, transparent, and accountable public sector governance. Various integrity assessment instruments have been implemented in the public sector in Indonesia, such as the Integrity Assessment Survey (SPI) by the Corruption Eradication Commission (KPK), the Integrity Zone (ZI) by the Ministry of Administrative and Bureaucratic Reform (PANRB), and IntoSAINT developed by INTOSAI. However, all three still have limitations. This study aims to analyze the strengths and weaknesses of these three instruments and develop an alternative assessment tool, the Integrity Assessment Tool (IAT), which can be an alternative choice to the integrity assessment model in Indonesia. This study uses a qualitative descriptive approach through literature studies and analysis of integrity policy documents, with a theoretical foundation of the OECD Integrity Framework and the Anti-Bribery Management System (SNI ISO 37001). The results show that the Integrity Assessment Tool is able to assess organizational integrity comprehensively and objectively through four main dimensions: history, performance, potential, and perception. This approach integrates quantitative, qualitative, and psychometric aspects to produce a more accurate and sustainable picture of the integrity position of public sector organizations. Theoretically, this research enriches the study of public sector integrity management, while practically, it provides guidance for government agencies in building a measurable, systematic, and sustainable integrity evaluation system as a basis for establishing a national model for integrity assessment.